Experimental and numerical study of flexural behavior of novel oil palm concrete filled steel tube exposed to elevated temperature - Javed, Muhammad Faisal; Ramli Sulong, Nor Hafizah; Memon, Shazim Ali; Rehman, Sardar Kashif-ur; Khan, Niaz Bahadur (Elsevier, 2018)
Oil palm boiler clinker (OPB) is a waste byproduct obtained at elevated temperature in an oil palm processing mill. Moreover, in recent years, Concrete filled steel tube (CFST) has been used widely in structures throughout the world. This paper presents an experimental and numerical study on novel sustainable composite beam by using OPB as replacement of natural coarse aggregate in CFSTs. Steel hollow beams (3.2 m length) infilled with natural aggregate concrete and OPB concrete were subjected to flexural load and elevated temperature. The parameters selected for the experimental tests were the cross-section type (square, rectangular) and the infilling type (natural aggregate concrete and OPB concrete). The thermal response, failure modes, critical temperature, temperature distribution in steel tube and infilled concrete, deflection along the span and fire concrete contribution ratio were evaluated. The critical temperature and fire concrete contribution ratio of OPB CFST was found to be higher than natural aggregate CFST, showing superior performance of OPB CFST. Thereafter, simulations were performed and more than 50 models were analyzed to evaluate the effect of yield strength of steel (235–400 MPa), compressive strength of infilled concrete (30–75 MPa), load ratio (0.3–0.6), width-to-depth ratio (2–0.5) and steel ratio (4.4%–2.1%) on the fire resistance time of CFST beam. It was found that the increase in load ratio, steel ratio and yield strength of steel has adverse effected on the fire resistance (FR) time of CFST member. However, the FR time increased significantly with an increase in compressive strength of infilled concrete and cross-sectional dimension of CFST member. Finally, the experimental results were compared with existing equations for CFST columns filled with natural aggregate concrete. It was found that current equations may underestimate the fire resistance of CFST filled with OPB.